Modern approaches and methods of introduction of innovative technologies in education and scientific activity - Yushchuk, Inna; Ovcharuk, Vladimir; Seidykh, Olga; Vovkodav (Obizyuk), Natalia; Andriiuk, Ihor (My University, 2018)
Experience of innovation activity of Ukrainian higher educational establishments confirms their ability to adapt to market requirements and to produce innovative products that are in demand using the results of this production to improve their educational and scientific work. The paper considers modern approaches and methods of introducing innovative technologies in education and research.
Keywords: вища освіта; інформаційно-комунікаційні технології; навчальний процес; higher education; information and communication technologies; educational process; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки